Analyzing spatial-temporal variability of ice motion in Northeast Greenland from 1985 to 2018 - Lu, Xi; Jiang, Liming; Xiao, Cunde; Li, Daan (Frontiers in Earth Science, 2022)
The Northeast Greenland Ice Stream (NEGIS), the largest basin in Greenland, is undergoing rapid and sustained dynamic change. However, the ice-flow behaviours over decadal timescales and the impacts of ice geometry and hydrology remain poorly understood. Here, we investigated the spatial and temporal characteristics of ice motions of three branches in NEGIS between 1985 and 2018 in response to bed topographic features and surface meltwater runoff based on 33 years of annual ice velocities derived from the satellite image of Landsat series. Spatial heterogeneities in ice velocity were found in three glaciers and were correlated with subglacial topography. Specifically, the peak velocities of both Nioghalvfjerdsfjorden and Zachariæ Isstrøm glaciers occur near the grounding line zone, where tidewater acts as a crucial force causing ice retreat, subglacial melting, and further acceleration. While for the Storstrømmen glacier, changes in the slope of the ice bed might cause an increase in ice motion in its inland segment. The temporal variability of ice velocity for both Nioghalvfjerdsfjorden and Zachariæ Isstrøm glaciers shows a clear regional speedup, with a mean increase of 14.60% and 9.40% in 2001–2018 compared to 1985–2000, but a widespread slowing of Storstrømmen glacier with a mean of 16.30%, which were related to a 184% surface runoff increase. This hydrodynamic coupling on ice motion over decadal timescales in these three glaciers is in line with previous studies on short-term acceleration in NEGIS induced by surface melt, not in agreement with negative feedback between enhanced surface meltwater production and ice motion previously reported in the southwest Greenland ice stream. Our work highlights crucial roles of subglacial topography and surface runoff on ice motion, which helps to promote understanding of dynamic changes of NEGIS response to changing atmospheric circumstances.